Hiperrealitas dalam Penggunaan Smartphone pada Kalangan Remaja - Febby Fitriani; Alfan Miko; Maihasni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Smartphones provide various instant messenger and social media applications that can facilitate communication and information. However, behind these benefits, hyperreality is currently occurring and there are many consequences that arise. Therefore, the main problem is How is hyperreality in smartphone use among teenagers. The purpose of this study is to determine the form of hyperreality and the consequences of smartphone use through instant messenger and social media among teenagers.This study uses a qualitative method. The data collection process is carried out using observation and in-depth interview techniques. In analyzing the data, the researcher uses qualitative analysis techniques. The theory used in this study is the theory of hyperreality proposed by Jean Baudrillard.The results of this research show that there are several forms of hyperreality of smartphone use via instant messenger and social media among teenagers which are seen through two Baudrillard concepts, namely simulation and simulacra. The simulation found is living in a digital simulation, acronyms and emoticons lose their reference and are obsessed with making friends in cyberspace. The simulacra found are blurring self-identity, changing use values to sign values, blurring the real world, chasing instant popularity, displaying falsehoods. Meanwhile, there are two consequences of smartphone use among teenagers. First, positive consequences, namely earning income and improving academic achievement. Second, negative consequences, namely reducing academic achievement, changing adolescent behavior, wasteful and uncertain time.